PERAN TUTOR DALAM PROSES PERKEMBANGAN SOSIAL ANAK USIA DINI DI PLATGROUP ISLAM EL-AKHYAAR CITEUREUP - Amelia Putri; Musa, Safuri; Santika, Tika (IKIP Siliwangi, 2025)
This study aims to describe the role of tutors, the impact, and the factors that influence early childhood social development. This playgroup is designed to be an appropriate environment for play, aiding in the growth and development of children, particularly in their social development. Harlock (1978), as cited in Khadijah and Jf (2021:12), states that